Osteogenic differentiation of human MSCs: Specific occupancy of the mitochondrial DNA by NFATc1 transcription factor. (July 2015) - Lambertini, Elisabetta; Penolazzi, Letizia; Morganti, Claudia; Lisignoli, Gina; Zini, Nicoletta; Angelozzi, Marco; Bonora, Massimo; Ferroni, Letizia; Pinton, Paolo; Zavan, Barbara; Piva, Roberta
Abstract: A substantial body of evidence indicates that mitochondrial morphology and function change during osteogenic differentiation. However, molecular mechanisms linking mitochondrial dynamics with the regulation of osteoblast functions are poorly understood. Amongst the molecules that influence the decision of human mesenchymal stem cells (hMSCs) to become osteoblasts are Slug and NFATc1 transcription factors (TFs). These molecules also interfere with different mitochondria-dependent pathways in response to a variety of cellular demands. The present study investigated the recruitment of Slug and NFATc1 at the D-loop regulatory region of mitochondrial DNA (mtDNA) in osteogenic differentiated hMSCs with the aim of exploring whether Slug and NFATc1 also act as mitoTFs in the mitochondrial pool of nuclear TFs. The results demonstrate that NFATc1, but not Slug, is localized in the mitochondria. Using chromatin immunoprecipitation assay, we found that NFATc1 is recruited at mtDNA, but this occurs only when the calcification process is at its highest in osteo-induced MSC and the maximum level of differentiation is reached. Occupancy of the mtDNA by NFATc1 is associated with a decreased expression of crucial mitochondrial genes such as Cytochrome B and NADH dehydrogenase 1. This suggests that NFATc1 acts as a negative regulator of mtDNA transcription during the calcification process and interruption of aerobic energy demand. The finding of NFATc1 participation in osteogenic differentiation through its direct involvement in the regulatory machinery of mitochondria suggests a new role for this TF and adds information on communication between mitochondrial and nuclear genomes.